EFFECT OF REDUCED BEAM SECTION IN STAGGERED TRUSS FRAME STRUCTURE VIERENDEEL ELEMENT WITH EARTHQUAKE LOAD ANALYSIS - M. Farid Nurul Iman; Endah Wahyuni; Data Iranata (Institut Teknologi Sepuluh Nopember (ITS), 2017)
The purpose of this study is to describe the effect of Reduced Beam Section in vierendeel panel element in STFsystem’s inelastic behavior based on earthquake load analysis. STF system is applied to 4, 6, and 10 storey building thatserved as office building. The structure’s system used Special Moment Resisting Frame (SMRF) system in longitudinaldirection (W-E) and STF system in transversal direction (N-S). The analysis method that used in this study is nonlinearpushover analysis. Application of RBS in vierendeel panel element showed that by the increasing of storey number, theductility of the structure was increased in both directions, while N-S direction has bigger ductility than W-E direction.Dissipation energy of the structure was also increased, especially in N-S direction. The first yielding process occurred invierendeel panel element, and then followed by truss and diagonal chord around vierendeel panel element, while the criticalcondition showed still at life safety level